ความชุกและปัจจัยที่เกี่ยวข้องกับอาการผิดปกติของระบบทางเดินหายใจ ในพนักงานกวาดถนน กรุงเทพมหานคร - ปลื้มใจ โชติกเดชาณรงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
This research is a cross-sectional study conducted in a sample group of 341 street sweepers in Bangkok, selected by a multi-stage sampling method. The study was conducted during February and April 2023. Data collection included questionnaires on personal factors, non-occupational air pollutant exposure factors, work-related factors, and environmental factors in the workplace. Abnormal respiratory symptoms in the past 6 months were collected using a questionnaire applied from the British Medical Research Council. The results showed that the prevalence of chronic respiratory symptoms in street sweepers in Bangkok was 33.7 %. The most common chronic respiratory symptom was cough with a prevalence of 22.0 %. Most workers consistently wore respiratory protective equipment. Statistically significant factors associated with chronic respiratory symptoms included exposure to secondhand smoke (aOR = 2.34, 95% CI: 1.30 - 4.23) and having part-time jobs or hobbies involving exposure to air pollutants (aOR=2.97, 95% CI: 1.33 - 6.63). Therefore, stakeholders should prioritize the prevention of abnormal respiratory symptoms among street sweepers. This can be achieved by monitoring respiratory symptoms, increasing awareness about secondhand smoke hazards, and using proper respiratory protective equipment during activities that expose individuals to indoor air pollutants.